Learning Interactions as it Evolves in a Social Learning Management System - Llantos, Orven E (Archīum Ateneo, 2021)
Human interaction is a result of an interplay between two or more entities where the interplay is a form of behavior response manifested as a physical or verbal reaction. In an online learning environment, the learning interaction studied are the interactions between the teacher and the students where interaction is seen in how one agent responds or reacts to the action of the other person. This paper tries to discover the dynamism of social networks in a social LMS environment with multiple actors including the principal, teacher, parent, and student as agents. Social network analysis was applied on the interaction data sourced from the deployment of my.eskwela, a locally developed social learning management platform, between October 15, 2019 and January 31, 2020 where learning interactions were observed during student assessment and evaluation and regular teaching sessions. Results showed increased collaboration over time. The principal's presence significantly contributed to the addition of activity nodes in the network and is considered the gatekeeper and trusted node with centrality scores of 0.174 and 0.964, respectively. Network density is less in a social network with imposed organizational hierarchy. This study contributes to the understanding of the evolving interactions where multiple stakeholders are collaborating in online learning environments.